Antibacterial performance of a porous Cu-bearing titanium alloy by laser additive manufacturing - Xu, Jiawei; Lu, Yanjin; Pan, Xiyun; Zhan, Desong; Wang, Qiang; Zhang, Ning (Frontiers in Bioengineering and Biotechnology, 2023)
Porphyromonas gingivalis (P. gingivalis) is the most common species that causes peri-implantitis. It forms an irreversible dense biofilm and causes inflammation. A novel 3D-printed porous TC4-6Cu alloy was fabricated using selective laser melting (SLM) technology for the dental implant, which is anticipated to inhibit biofilm formation. This work used scanning electron microscopy (SEM) and laser confocal microscopy (CLSM) to detect the antimicrobial ability of the alloy against sessile P. gingivalis. Plate antimicrobial counting experiments showed that the antibacterial rates of the alloy against adherent bacteria and planktonic bacteria after 24h were 98.05% and 73.92%, respectively. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of Cu2+ were tested to appraise the antibacterial property of the alloy against planktonic P. gingivalis. The relationship between the antibacterial mechanism of the alloy with oxidative stress was evaluated through ROS fluorescence intensity and protein leakage concentration. The results revealed that the alloy significantly eliminated adherent bacteria and inhibited biofilm formation. Moreover, 3D-printed porous TC4-6Cu alloy demonstrated significant bactericidal ability by inducing the production of reactive oxygen species (ROS), which could result in protein leakage from the bacterial cell membrane.